Wet chemistry approach to the preparation of tantalum-doped hydroxyapatite: Dopant content effects - Baradaran, Saeid; Nasiri-Tabrizi, Bahman; Seyed Shirazi, Seyed Farid; Saber-Samandari, Saeed; Shahtalebi, S.; Basirun, Wan Jefrey (Elsevier, 2018)
Tantalum-doped hydroxyapatite (Ta-doped HA) nanopowders with different Ta contents were synthesized by a wet-chemical precipitation route. The structure modification and charge compensation mechanism were investigated by various characterization techniques. Due to the smaller size of tantalum ions compared to the Ca2+ size, it was assumed that the tantalum ions occupy either the Ca2+ and/or the interstitial positions in the HA lattice, where the charge imbalance from to this substitution was compensated by the Ca2+ vacancies. From the XRD patterns, the as-synthesized nanopowders were poorly crystalline apatite in the absence and presence of different dopant contents. The hexagonal HA and tricalcium phosphate (β-TCP) phases as biphasic calcium phosphate mixtures were formed after heating at 900 °C. In addition to the β-TCP phase, minor extra phases such as calcium oxide (CaO) and calcium pyrophosphate (Ca2P2O7) were identified from the HA decomposition. The FTIR results indicated that the decrease of structural hydroxyl groups depended on both tantalum oxyanions and carbonate contents. In the XPS profile, the Ta 4 f peak of the doped sample could be decomposed into four main components, which showed different oxidation states for tantalum (TaO2 oxide). According to the TEM observations, the doped calcined powder at 900 °C was composed of uniform nanoneedles with an average length and width of 120 ± 50 and 10 ± 5 nm, respectively.